Development of a decision aid for the treatment of benign prostatic hyperplasia: A four stage method using a Delphi consensus study. Issue 7 (July 2016) - Lamers, Romy E.D.; Cuypers, Maarten; Garvelink, Mirjam M.; de Vries, Marieke; Bosch, J.L.H. Ruud; Kil, Paul J.M.
Highlights: A LUTS/BPH 1 decision aid was developed in following a structured 4 stage method. A Delphi consensus study was used to reach consensus between urologists on medical content. By involving urologists and patients in development we aim to facilitate implementation. This 4 stage method can be adopted to support other medical decision issues. Abstract: Objective: To develop a web-based decision aid (DA) for the treatment of lower urinary tract symptoms due to benign prostatic hyperplasia (LUTS/BPH). Methods: From February–September 2014 we performed a four-stage development method: 1: Two-round Delphi consensus method among urologists, 2: Identifying patients' needs and expectations, 3: Development of DA content and structure, 4: Usability testing with LUTS/BPH patients. Results: 1 ( N = 15): Dutch urologists reached consensus on 61% of the statements concerning users ' criteria, decision options, structure, and medical content . 2 ( N = 24): Consensus was reached in 69% on statements concerning the need for improvement of information provision, the need for DA development and that the DA should clarify patients ' preferences . 3: DA development based on results from stage 1 and stage 2. 4 ( N = 10): Pros of the DA were clear information provision, systematic design and easy to read and re-read. Conclusion: A LUTS/BPH DA containing VCEs ** was developed in cooperation with urologists and patients following a structured 4 stage method and was stated to be well accepted. Practice Implications: This method can be adopted for the development of DAs to support other medical decision issues.